Gender and decision-making in agriculture: a case study of groundnuts farmers in Zambia - Kasanda, Ednah (Kansas State University, 2017)
Zambia’s government and its development partners continue to be challenged with how to adequately address the seeming gender inequity in Zambia’s agricultural sector. Women in Zambia’s agricultural sector face challenges in accessing resources and opportunities that could enhance their welfare. In addition, cited inequitable distribution of power in decision-making have been assumed to hamper women’s ability to enhance their own economic wellbeing. Therefore, understanding the factors that influence women’s decision-making in agriculture and how these factors contribute to their wellbeing can provide insights into how to develop programs that help improve their economic wellbeing. This thesis assessed the decision-making and production activities by women in Zambia’s agriculture using the groundnuts subsector as a case study. It used data from the nationally representative Rural Agricultural Livelihood Survey 2015 (RALS15), drawing a sample of rural groundnut farmers and employed a statistical and econometric analysis to explore the relationships of specific factors on women in the groundnut subsector. The following are the key findings: i. Women make up 38% of the producers in Zambia’s groundnuts subsector but accounted for 49% of the total number of people controlling groundnut selling decisions. Women accounted for 48% of the total people controlling how income from groundnut sales are used. These distributions would challenge the prevailing perception that women have a decreasing control over decision-making as one moves from production to utilization of the income from production, at least in the case of the groundnut subsector in Zambia’s agricultural sector. ii. The factors influencing women’s control over production include the gender of the household head, region, affiliation to women’s groups, distance between the homestead and extension service access point, distance between the homestead and the field plot, the woman’s education and household’s production assets. For example, a percentage increase in the distance to field plot reduced the women’s control by one-seventh of a percent. Similarly, the more educated the woman is, the less their control over groundnut production is. iii. Furthermore, groundnut commercialization did not seem to influence female control over production. The foregoing challenges some of the conclusions from previous research regarding women’s control over production decisions. It is possible that the position of groundnuts in Zambian agriculture could be an explanatory factor the results. However, it was not tested. Therefore, it is suggested that future studies explore the relationship between the crop and the empowerment women experience from its production.
Keywords: Groundnuts; Gender; Agriculture; Zambia